Pengaruh Citra Merek dan Desain Produk serta Harga Terhadap Keputusan Pembelian Sepatu Lari Ortuseight di Kota Samarinda - Toto Priyo; Purwadi Purwadi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2025)
This study aims to analyze the effect of brand image, product design, and price on purchasing decisions of Ortuseight running shoes in Samarinda City. A quantitative approach was employed with 110 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS 29. The results indicate that brand image, product design, and price have a positive and significant effect on purchasing decisions. Simultaneously, the three variables significantly influence purchasing decisions with a coefficient of determination (R²) of 0.608. These findings suggest that a strong brand image, attractive product design, and appropriate pricing can increase consumer purchasing decisions for Ortuseight running shoes in Samarinda City.